Educational supply chain sustainability - Nur Shahida, Mat Ishah; Lee, Khai Loon; Gusman, Nawanir (Emerald Group Publishing Ltd., 2023)
Purpose: The purpose of the paper is to determine the importance of digital literacy (DL) in educational supply chain (EduSC) sustainability. Design/methodology/approach: A semi-systematic review technique was used with Google Scholar and Scopus databases. Findings: The growing use of technology and digital resources revealed a significant digital divide between people, educational processes and access to technologies and suitable infrastructures, as well as the need for DL, particularly in the EduSC in the 21st century. According to the results, just 58.6% of EduSC researchers emphasize economic sustainability, while 72.4% emphasize environmental sustainability. A total of 93.1% of scholars examine the impact of DL on society, demonstrating the significance of DL in the EduSC. Originality/value: DL was discovered to have the greatest impact on society, with students and educators being related to all processes in an EduSC.